Incidence and Risk Factors of Hypomagnesemia in Head and Neck Cancer Patients Treated with Cetuximab - Enokida, Tomohiro; Suzuki, Shinya; Wakasugi, Tetsuro; Yamazaki, Tomoko; Okano, Susumu; Tahara, Makoto (Frontiers in Oncology, 2016)
Background Hypomagnesemia is a common adverse event during cetuximab (Cmab) treatment. However, few reports have investigated the incidence and risk factors of hypomagnesemia in head and neck cancer patients treated with Cmab. Methods We retrospectively reviewed 131 head and neck cancer patients who received Cmab-containing therapy. Main eligibility criteria were ≥3 Cmab administrations, no prior EGFR-directed therapy, and no prophylactic Mg supplementation. Results Median baseline serum Mg level and number of Cmab administrations were 2.2 mg/dl and eight, respectively. Overall incidence of hypomagnesemia was 50.4% (grade 1, 46.6%; grade 2, 3.1%; grade 3, 0%; grade 4, 0.8%) and differed between patients treated with palliative chemotherapy and bioradiation (Cmab and radiation) (63% vs. 24%; p<0.01). Independent risk factors were low baseline serum Mg [Odds ratio (OR) 161.988, 95% confidence interval (CI) 9.436-2780.895], ≥7 Cmab administrations (OR 3.56, 95% CI 1.16-13.98), and concurrent administration of platinum (cisplatin; OR 23.695, 95% CI 5.219-107.574, carboplatin; OR 5.487, 95% CI 1.831-16.439). Respective incidence of hypomagnesemia in patients in high- (concurrent platinum and ≥7 Cmab administrations) and low-risk (no concurrent platinum and <7 Cmab administrations) groups was 66.0% and 6.6% (P<0.001, OR 28.0). Conclusion Cmab is associated with a significant risk of hypomagnesemia in patients with head and neck cancer with longer term administration and concurrent platinum therapy. High-risk patients should be treated with particular care.